Pengaruh Pengeluaran Non Makanan Per Kapita, Tingkat Kemiskinan, dan Perempuan Sebagai Tenaga Profesional Terhadap IPM Di Provinsi Lampung Periode 2017-2021 - Chairunnisa Chairunnisa; Toto Gunarto (Journal on Education, 2023)
The strategic location of Lampung Province on Sumatra Island does not merely make human development in Lampung Province more advanced than other provinces on Sumatra Island. This is evidenced by the HDI figure in Lampung Province which is still considered the lowest in Sumatra and even below the average HDI in Indonesia. This study used data from 15 regencies/cities in Lampung Province for the 2017-2021 period, using the panel data regression method, with the chosen model, namely the Fixed Effect Model (FEM). The purpose of this study was to find out how non-food expenditure, poverty levels, and women as professionals influence HDI in Lampung Province for the 2017-2021 period. The results of this study indicate that 1) Non-food expenditure has a positive and significant effect on HDI in Lampung Province, 2) Poverty level has a negative and significant effect on HDI in Lampung Province, 3) Women as Professionals have no significant and positive effect on HDI in Province Lampung.